Pengaruh Penggunaan ChatGPT Terhadap Hasil Belajar Siswa SMP - Palma Juanta; Yapriani Damenta Sidabutar; Tisa Kiranta Br Tarigan; Triyani Vianny Silalahi (Jejak digital: Jurnal Ilmiah Multidisiplin, 2026)
The rapid development of Artificial Intelligence (AI) technology, particularly ChatGPT, has created various opportunities in the field of education. This study aims to examine the effect of ChatGPT usage on junior high school students’ cognitive learning outcomes and to compare students’ learning outcomes when completing tasks without ChatGPT and with ChatGPT assistance. The research employed a quantitative approach using a quasi-experimental method with a one-group comparison design. The sample consisted of 34 eighth-grade students of Dr. Wahidin Sudirohusodo Private Junior High School, Medan, selected through purposive sampling. Data were collected using learning achievement tests and a ChatGPT usage questionnaire. The data were analyzed using descriptive statistics, validity testing, reliability testing, the Shapiro–Wilk normality test, and the Paired Sample t-test with the assistance of IBM SPSS Statistics 25. The results showed that the mean score of students’ learning outcomes without ChatGPT was 87.12, while the mean score with ChatGPT assistance was 94.99. The Paired Sample t-test revealed a significance value of 0.000 (< 0.05), indicating that ChatGPT usage had a significant effect on students’ learning outcomes. These findings suggest that the appropriate use of ChatGPT can improve students’ cognitive learning achievement. However, its use should be properly supervised to prevent overdependence and to maintain students’ independent thinking skills.